Opaque Technologies - Parra Cancino, Juan (Karlsruhe Hochschule für Musik, Karlsruhe, 2024)
Harald Bode reconstructed instruments
Workshop and lecture for the faculty and Students of the Hochschule für Musik, Karlsruhe
FRIS
Editorial review
Keywords: Music, Thought and Technology